Measurement and Analysis of US tight oil Determinants. An applied study for the period (2004-2019) - Ali Al-Anezi, Wisam H.; Attallah Faihan, Mamdooh; Ali Hamad, Abed (Opción, 2019)
This study aims to demonstrate knowledge of the factors determining the production of American shale oil during the period (2004-2019), as (global demand for crude oil, global crude oil supply, West Texas oil prices, global growth rate and world population) were used as factors Shale oil production was determined, and the VECM model was used to analyze the long and short term relationship and the results demonstrated that there is a long-term bal- ance relationship between all independent variables and shale production as a dependent variable except for the global demand variables for crude oil and the reason may be that the changes That you get in the global demand for Aft crude is absorbed through changes in crude oil production without compro- mising the US shale oil, and the global variable as the growth of the changes that you get this variable may affect the quantities produced and sold crude oil as well.